2019
DOI: 10.1111/hdi.12723
|View full text |Cite
|
Sign up to set email alerts
|

Early withdrawal and non‐withdrawal death in the months following hemodialysis initiation: A retrospective cohort analysis

Abstract: Introduction: Whether and how factors associated with elective hemodialysis withdrawal differ from those associated with non‐withdrawal death soon after maintenance hemodialysis initiation have not been well studied. Methods: A retrospective cohort analysis was performed using USRDS data from 2011 to 2014. Patients were randomly categorized 2:1 into training and validation samples. Elective withdrawal deaths were identified using the Death Notification form. Multinomial logistic regression was used to fit a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Caucasians have been reported to have a greater risk of dialysis withdrawal attributed to social supports and cultural acceptance of treatment withdrawal [ 24 , 42 ]. Although our study showed similar findings, it is difficult to ascertain the correlation due to the high proportion (70%) of Caucasian dialysis patients in Australia, which was also observed in other dialysis withdrawal studies [ 6 , 13 , 24 ]. In many non-Western countries, dialysis initiation and withdrawal may not be based on patients’ preferences, due to systemic differences in dialysis resources, palliative care access and ethico-legal regulations [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Caucasians have been reported to have a greater risk of dialysis withdrawal attributed to social supports and cultural acceptance of treatment withdrawal [ 24 , 42 ]. Although our study showed similar findings, it is difficult to ascertain the correlation due to the high proportion (70%) of Caucasian dialysis patients in Australia, which was also observed in other dialysis withdrawal studies [ 6 , 13 , 24 ]. In many non-Western countries, dialysis initiation and withdrawal may not be based on patients’ preferences, due to systemic differences in dialysis resources, palliative care access and ethico-legal regulations [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 53%
“…Early mortality after dialysis initiation is known to be high [ 10–12 ]. A recent US Renal Data System (USRDS) registry study suggested that the risk factors associated with death from dialysis withdrawal were similar to other causes of death within 6-month post-initiation of haemodialysis (HD) [ 13 ]. Risk factors associated with death from cause-specific withdrawals have not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 and Table 1 provide a summary of the definitions of dialysis withdrawal classified by the reasons for withdrawal and causes of death. Country‐specific registry studies often define dialysis withdrawal by reasons for withdrawal, irrespective of the underlying cause of death by kidney failure or comorbid conditions, 5,23–32 with the exception of the United States Renal Data System 2,33–36 . Dialysis withdrawal is classified as per reporting personnel in registries, and the risk of misclassification and oversimplification is high, especially when only a single cause of death is reported without the details of death.…”
Section: Dialysis Withdrawalmentioning
confidence: 99%
“…United States Renal Data System (USRDS) Wetmore et al, 2018 33 Wetmore et al, 2019 34 Wetmore et al, 2020 35 Roberts et al, 2021 36 …”
Section: Dialysis Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation